Effects of Mother Tongue Instruction on Students Mathematical Achievement in the Bekwai Municipal, Ghana - Abdul-Ganiyu, Fuseini; Adu Obeng, Benjamin; Asare, Bright; Dissou Arthur, Yarhands (Golden Ratio of Social Science and Education, 2024)
The study examined the effect of the mother tongue teaching on students' mathematical achievement. From St. Joseph Senior High Technical School, two experimental classes and one control class were chosen. While the control group was instructed only in English, the first experimental group was instructed exclusively in their native language (Twi), whereas the second experimental class was instructed using mother tongue (Twi) as an additional medium of instruction. The results of the pre-test and post-test were statistically examined using the t-test. The findings showed that using Twi as the sole teaching language and using English as the only training language were equally unsuccessful, while mother tongue (Twi) was found to be statistically significant in improving students’ mathematics achievement.